Cisplatin Promotes the Efficacy of Immune Checkpoint Inhibitor Therapy by Inducing Ferroptosis and Activating Neutrophils - Ziwei Zhou; Yiming Zhao; Yiming Zhao; Si Chen; Guohui Cui; Wenkui Fu; Shouying Li; Xiaorong Lin; Xiaorong Lin; Hai Hu (Frontiers Media S.A., 2022)
The combination of immunotherapy with platinum-based chemotherapy has become the first-line treatment for patients with advanced non-small cell lung cancer (NSCLC) with negative driver gene mutations. However, finding an ideal chemotherapeutic regimen for immunotherapy and exploring the underlying mechanism have noticeably attracted clinicians' attention. In this study, we found that cisplatin induced ferroptosis of tumor cells, followed by N1 neutrophil polarization in the tumor microenvironment, which in turn remodeled the "cold" tumor to a "hot" one through enhancing T-cell infiltration and Th1 differentiation. Based on the important role of tumor ferroptosis in the immune-promoting effect of cisplatin, we noticed that the combination of a ferroptosis activator showed a synergistic effect with chemoimmunotherapy of epidermal growth factor receptor (EGFR)-mutant NSCLC, which would be an effective strategy to overcome immunotherapy resistance in NSCLC patients harboring driver mutations.